Investigating the Effects of Gender on Consumers’ Moral Philosophies and Ethical Intentions - Bateman, Connie R. (Journal of business ethics, 2010)
Using information collected from a convenience sample of graduate and undergraduate students affiliated with a Midwestern university in the United States, this study determined the extent to which gender (defined as sex differences) is related to consumers’ moral philosophies and ethical intentions. Multivariate and univariate results indicated that women were more inclined than men to utilize both consequence-based and rule-based moral philosophies in questionable consumption situations. In addition, women placed more importance on an overall moral philosophy than did men, and women had higher intentions to behave ethically. The marketing and practical implications of these findings are discussed, and the limitations of the research are presented along with several suggestions for future inquiry, which could advance current understanding of consumer ethics.